Mathematical Model of Growth in The Number of Students in NTB Using Newton-Gregory Polynomial Method - Habib Ratu Perwira Negara; Malik Ibrahim; Kiki Riska Ayu Kurniawati (Universitas Bumigora, 2020)
This research aims to find out the mathematical model and predict the growth in the number of elementary, junior high, high school, and vocational school students in NTB Province, using the Newton-Gregory Advanced Polynomial method. The result of simulating the predicted growth of the number of elementary school students in NTB in 2020 is 319565, with MAD at 353178, MSE at 1247346996840, MAPE at 68,655. Then for the predicted growth of the number of junior high school students in NTB in 2020 of 165141 with MAD of 1876271.7, MSE amounted to 3520395492220, MAPE amounted to at 1077.7039. Furthermore, the predicted growth of the number of high school students in NTB was 399679 with MAD of 44154, MSE of 19495757160, MAPE of 42.0719. while for the results of the simulation of predicted growth in the number of vocational school students in NTB in 2020 is 3738854 with MAD of 393779, MSE amounted to 15506190084.1, MAPE amounted to 49.2027. Based on the results of this study can state that Newton-Gregory Interpolation advanced by using GUI on Matlab, can predict the growing number of elementary, junior high, high school, and vocational students in NTB by using data on the number of students in 2009-2019 and obtained mathematical models of elementary, junior high, high school, and vocational school growth.